Artefacts of Cognition: the Use of Clay Tokens in a Neo-Assyrian Provincial Administration. Issue 2 (2nd July 2014) - MacGinnis, John; Willis Monroe, M.; Wicke, Dirk; Matney, Timothy
Abstract : The study of clay tokens in the Ancient Near East has focused, for the most part, on their role as antecedents to the cuneiform script. Starting with Pierre Amiet and Maurice Lambert in the 1960s the theory was put forward that tokens, or calculi, represent an early cognitive attempt at recording. This theory was taken up by Denise Schmandt-Besserat who studied a large diachronic corpus of Near Eastern tokens. Since then little has been written except in response to Schmandt-Besserat's writings. Most discussions of tokens have generally focused on the time period between the eighth and fourth millennium bc with the assumption that token use drops off as writing gains ground in administrative contexts. Now excavations in southeastern Turkey at the site of Ziyaret Tepe — the Neo-Assyrian provincial capital Tušhan — have uncovered a corpus of tokens dating to the first millennium bc. This is a significant new contribution to the documented material. These tokens are found in association with a range of other artefacts of administrative culture — tablets, dockets, sealings and weights — in a manner which indicates that they had cognitive value concurrent with the cuneiform writing system and suggests that tokens were an important tool in Neo-Assyrian imperial administration.